2019
DOI: 10.1016/j.jtho.2019.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Classification of Neuroendocrine Tumors of the Thymus

Abstract: Introduction:The WHO classification of pulmonary neuroendocrine tumors (PNETs) is also used to classify thymic NETs (TNETs) into typical and atypical carcinoid (TC and AC), large cell neuroendocrine carcinoma (LCNEC), and small cell carcinoma (SCC), but little is known about the usability of alternative classification systems.Methods: One hundred seven TNET (22 TC, 51 AC, 28 LCNEC, and 6 SCC) from 103 patients were classified according to the WHO, the European Neuroendocrine Tumor Society, and a grading-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 38 publications
(49 reference statements)
1
53
0
4
Order By: Relevance
“…Subsequently, in a pilot study carried out on the egfr microsatellite CA-SSR-1 performed by the first genetic analyzer available in pathology, Thermo Fisher's 3130 genetic analyzer, we were able to show that CA-SSR-1 allelic imbalance with short allele relative prevalence significantly correlated with EGFR 3+ immunohistochemical scores, increased egfr gene copy numbers, and advanced stage with relapsing/metastatic behavior in thymomas (44). More recently, we have established further collaborations with other in-house research units (43) and national (19,42,54) and international institutes (55,56). Thanks to frequent participation in meetings and interfacing with members of the scientific community at major conferences on thymic tumors, as well as holding structured workgroups supported by the scientific society ITMIG, our boundaries have changed and widened.…”
Section: Pathological Tet Evaluation and Research Activitiesmentioning
confidence: 82%
“…Subsequently, in a pilot study carried out on the egfr microsatellite CA-SSR-1 performed by the first genetic analyzer available in pathology, Thermo Fisher's 3130 genetic analyzer, we were able to show that CA-SSR-1 allelic imbalance with short allele relative prevalence significantly correlated with EGFR 3+ immunohistochemical scores, increased egfr gene copy numbers, and advanced stage with relapsing/metastatic behavior in thymomas (44). More recently, we have established further collaborations with other in-house research units (43) and national (19,42,54) and international institutes (55,56). Thanks to frequent participation in meetings and interfacing with members of the scientific community at major conferences on thymic tumors, as well as holding structured workgroups supported by the scientific society ITMIG, our boundaries have changed and widened.…”
Section: Pathological Tet Evaluation and Research Activitiesmentioning
confidence: 82%
“…Additionally, while this disease may display a relatively aggressive tumor biology in comparison to benign thymoma, optimal classification of these tumors has been challenging, resulting in several unique staging systems, and recent investigations to identify biomarkers which may further describe the disease and guide management (16). Given these unique criteria, staging and treatment should be evaluated in the context of all proposed staging models and any available molecular biomarkers which may aid in treatment optimization.…”
Section: Discussionmentioning
confidence: 99%
“…In stark contrast to thymomas, TNET have a high propensity for regional lymph node metastases and > 50% of patients show involvement of regional lymph nodes at diagnosis [38]. The histological subtype is prognostically relevant: 5-year survival rates decrease from 50-70% in TC and AC [8,22,30,32] to 30-66% in LCNEC [3-5, 9, 20, 24, 25, 29, 32, 36] and to 0% (median survival 13-26 months) in SCC [17,23,32,36,39]. The significant variation of published survival data in LCNEC is remarkable and points to a marked heterogeneity of the tumors analyzed.…”
Section: General Features Of Thymic Neuroendocrine Tumorsmentioning
confidence: 99%
“…There are few published data on genomic features of TNET [8,21,27,32] and virtually no data on the mutational spectrum of these tumors. One of the largest studies to date [32] using comparative whole-genome hybridization (CGH) found an incremental increase of genomic alterations from TC to AC and LCNEC/SCC that correlated with survival.…”
Section: Molecular Findings In Tnetmentioning
confidence: 99%